The Effect of Green Accounting, Profitability, and Media Exposure on Corporate Social Responsibility Disclosure (Empirical Study on LQ45 Index Companies for the 2019-2022 Period) - Rizky Nabila Tanjung; Sri Mayang; Muammar Khaddafi; Iswadi Iswadi (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
This study aims to test and find out how the effect of the implementation of Green Accounting, Profitability, and Media Exposure on Corporate Social Responsibility Disclosure (CSRDi) both directly and indirectly. The population of this study is LQ45 index companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The samples used in this study used the purposive sampling method. Based on the sample criteria determined, the number of samples obtained was 25 LQ45 index companies. To answer the problem in this study, the data was analyzed using multiple regression analysis with the help of the E-Views 12 application. The results of this study show that: 1) Green Accounting has a partial effect on Corporate Social Responsibility Disclosure, 2) Profitability does not have a partial effect on Corporate Social Responsibility Disclosure, 3) Media Exposure has a partial effect on Corporate Social Responsibility Disclosure and 4), Profitability and Media Exposure simultaneously has an influence on Corporate Social Responsibility Disclosure.